COCA CORPUS AND ITS PREFERENCES (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract The Corpus of Contemporary American English (COCA) stands as a pivotal resource in modern linguistic research, offering a vast and diverse collection of authentic language data